The challenges experienced by parents when parenting a child with hearing loss within a South African context. Issue 1 (1st January 2021) - Davids, Ronel; Roman, Nicolette; Schenck, Catherina
ABSTRACT: The purpose of the current study was to explore the challenges experienced by hearing parents when parenting a child with hearing loss. Using a qualitative purposive sampling design, interviews were conducted with 13 parents (9 mothers, 4 fathers) residing in Cape Town, South Africa. Four salient themes emerged, namely: 1) communication is difficult, hard, and frustrating; 2) lack of knowledge and information about hearing loss makes it difficult to parent; 3) little or no support makes for a lonely journey; and 4) support identified by parents for parents. The findings of the study have important implications for collaboration and partnerships between parents and health and family practitioners within South Africa for the design and development of supportive interventions for parents parenting a child with hearing loss.